THE YIELD AND QUALITY OF DRIED PRODUCE OF MELON VARIETIES DEPENDING ON DRYING METHODS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of a study of the growth, yield and quality of the fruits of melon varieties in the conditions of newly irrigated typical gray earth soils, as well as the yield, biochemical composition and quality of the dried produce of the studied varieties with various drying methods. It was revealed that the highest (26.9-36.8 t/ha) and high-quality (with a dry matter content in fruits of more than 14.0%, sugars - 12.0%) was obtained from summer varieties of melon Toshloki-862, Novotkalla, L-152, Kuk tinni-1087, Kundalang tur, Ok novvot, Obi novvot Samarkand local, Lazzatli, Oltin vodiy, Sahovat, Tuyona, Ich-kizil, Dilhush, Ok kovun-557, Kukcha-588. When drying melon varieties by the method of the solar dryer, the yield of dried products (melons) in relation to the pulp was 8.3-13.6%, the highest yield (10.4–13.6%) of dried products (melons) was obtained from Kundalang tur varieties, Toshloki-862, Ok novvot, Kuk tinni-1087, Ok urug-1157, Novotkalla, Kukcha-588, Tuyona, Sahovat, Oltin vodiy, Lazzatli, Shakarpalak-554, Ok kovun-557, Dilhush, Obi novvot Samarkand local, at the same time the yield of dried products (melons) was 2.71-4.11 t/ha. In the artificial drying method, the yield of dried produce (melon) by grades was 9.0-14.7%, and the highest yield (12.0-14.7%) of dried produce (melon) was obtained from the above grades and the yield was 3.40-4.73 t/ha. In the composition of dried products (melons) with an artificial method of drying, the content of dry matter (0.5-1.1%), sugars (0.6-2.8%), and vitamin C was higher in comparison with the solar method (2, 40-4.60 mg /%) and was rated 0.5-1.1 points higher.